APLIKASI ABSENSI GURU DAN SISWA SECARA ONLINE DENGAN MEREKAM WAJAH DAN DETEKSI LOKASI (STUDI KASUS : SMA NEGERI 2 MANDAU) - Leonard Tambunan; Novidawaty Tambunan (JSR : Jaringan Sistem Informasi Robotik, 2022)
An attendee list is an important thing in an institution or organization. With a good attendance system’s record, it is thought that it can assist the management to do controlling and measuring the achievement of an aim that has already been set before and also arrange all the workers to become effective. The student and teacher attendance system that has been running so far at SMA Negeri 2 Mandau is still recorded manually through the attendance list provided by the school operator. The problems so far are the difficulties of school operators in recapitulating teacher and student absenteeism monthly and due to the paper sheet, the files of attendance list that have been filled daily by students and teachers often get lost and have a risk to become damaged. Based on these problems, it is deemed required to create an application to make it easier for subject teachers or homeroom teachers to record themselves and students’ attendance at school and class. Teacher attendance can be accessed online by the teacher when doing participation in school every day. The attendance will be recorded at the time of entry and return from the school. In order to prevent cheating in recording teacher attendance, it is determined that every teacher attendance must activate the HP/Laptop camera feature and the location detection feature so that the system can automatically save photos of faces and their locations. For student attendance, attendance is carried out by the homeroom teacher. The homeroom teacher will attend to students based on their class before starting and ending learning activities. Furthermore, school operators can make print the recapitulation report on teacher and student absenteeism based on a certain period. With the application of teacher and student attendance, the problems that have occurred thus far at SMA Negeri 2 Mandau finally can be resolved properly.